2013
DOI: 10.1111/aogs.12173
|View full text |Cite
|
Sign up to set email alerts
|

Is home‐based pelvic floor muscle training effective in treatment of urinary incontinence after birth in primiparous women? A randomized controlled trial

Abstract: The results indicate that home-based PFMT is effective. However, written training instructions were as efficient as home-based training with follow up visits every sixth week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 27 publications
4
31
1
13
Order By: Relevance
“…A Swedish study by Alhund et al on home based PFMEs has shown very few drop outs from their exercise programme which is in contrast to the results of our study as majority of the participants dropped out from our study because of non adherence to recommended exercises [16].…”
Section: Discussioncontrasting
confidence: 99%
“…A Swedish study by Alhund et al on home based PFMEs has shown very few drop outs from their exercise programme which is in contrast to the results of our study as majority of the participants dropped out from our study because of non adherence to recommended exercises [16].…”
Section: Discussioncontrasting
confidence: 99%
“…A randomized controlled trail including100 primiparous women indicate that home-based pelvic floor muscle training is effective [31]. Another study showed that increasing awareness of pelvic floor muscle re-training in postpartum women with a weakened PFM may potentially reduce SUI and, as result, increase QoL [32].…”
Section: Discussionmentioning
confidence: 99%
“…23 In our setup we don't have the facility of trained physiotherapist, hence home-based exercises with intermittent supervision was done.…”
Section: Discussionmentioning
confidence: 99%